Tacrinas modificadas: síntese, derivatização e avaliação farmacológica de 7-amino-6-aril-6H-cromeno[4,3-b]quinolinas - Rocha, Inaiá Oliveira da (2025)
This work describes the synthesis of new structural analogues of tacrine (THA), making structural variations that could increase the efficacy of the drug and/or increase its possible area of action. Thus, this work describes the synthesis and study of the enzyme inhibitory properties of 7-amino-6-aryl-6H-chromeno[4,3-b]quinolines, an unprecedented series of hybrid heterocycles analogous to 9-amino-1,2,3,4-tetrahydroacridine (THA), which contains flavanones as structural modifiers, aimed at generating possible prodrugs for the treatment of Alzheimer's disease (AD). This work also presents a study of N-derivatization reactions aimed at the insertion of pyrroles, sulfonamides, amides and hydrazineyl, with the aim of investigating the reactivity of the amino group of these new THA hybrids, as well as investigating biological properties of interest. To this end, it was initially possible to synthesize and characterize 7- amino-6-aryl-6H-chromeno[4,3-b]quinoline compounds, derived from flavanones and 2- aminobenzonitriles as precursor blocks. In this way, six (6) new heterocycles analogous to THA were isolated and characterized in yields of 40-77%. Next, the new series of modified tacrines (7-amino-6-aryl-6H-chromeno[4,3-b]quinolines) were evaluated for their AChE and BChE inhibition activity in vitro. The experimental results of enzyme inhibition were added to complementary molecular docking studies, demonstrating that the compounds developed showed anti-ChEs properties, especially for BChE inhibition. The N-derivatization reactions enabled the construction of different derivatives, such as: the construction of 5 (five) new pyrroles derived via the Clauson-Kaas reaction, leading to the formation of 6-phenyl-7-(1Hpyrrole-1-yl)-6H-chromeno[4,3-b]quinolines; in the construction of 6 (six) new sulfonamides derived via the use of benzenesulfonyl chlorides, thus forming the compounds N-(6-phenyl6H-chromeno[4,3-b]quinolin-7-yl)benzenesulfonamides. Furthermore, by means of a targeted study using the compound 7-amino-6-phenyl-6H-chromeno[4,3-b]quinoline, it was possible to obtain 5 (five) new unpublished compounds, 2 (two) of which are new (N-benzoyl)-N-(6- phenyl-6H-chromeno[4,3-b]quinolin-7-yl)benzamides; 2 (two) new N-(N-di)-(prop-2-in-1-yl)- 6-aryl-6H-chromeno[4,3-b]quinolin-7-amines; and 1 (one) new 7-hydrazinyl-6-aryl-6Hchromeno[4,3-b]quinoline. The studies with compounds selected from the N-derivatizations for the enzymatic inhibition properties of AChE and BChE in vitro, indicated that the N-(6-aryl6H-chromeno[4,3-b]quinolin-7-yl)benzenesulfonamides and the 7-hydrazinyl-6-aryl-6Hchromeno[4,3-b]quinolines, showed promise as prototypes for new anticholinesterase drugs, and could be explored in future complementary anti-ChEs trials in vitro and in vivo. All the chemical compounds in the new series obtained in this thesis were characterized by melting point and structurally elucidated using routine spectroscopic and spectrometric techniques, such as one- ( 1H and 13C) and two-dimensional (HSQC and HMBC) NMR in solution and HRMS.